2018
DOI: 10.1016/j.jcrs.2018.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for refractive error after cataract surgery: Analysis of 282 811 cataract extractions reported to the European Registry of Quality Outcomes for cataract and refractive surgery

Abstract: Several risk factors (poor preoperative CDVA, ocular comorbidity, and previous eye surgery) were related to poor refractive outcomes after cataract extraction. When these risk factors are present, care should be taken with the preoperative examination and choice of IOL to avoid a refractive surprise. The average outcomes can be used as a refractive outcome benchmark.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
109
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(123 citation statements)
references
References 12 publications
9
109
0
5
Order By: Relevance
“…Patients included in our study were slightly younger, mean of 70.42 years, than those included in the 2013 (mean 73.9 years) and 2018 (mean 73.5 years) EUREQUO reports [6,7], with a majority of women. e percentage of eyes with prior pathologies and preoperative conditions increasing the surgical complexity (28.55% and 11.1% respectively) was similar in our study to those in the previous reports [6,9,10].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Patients included in our study were slightly younger, mean of 70.42 years, than those included in the 2013 (mean 73.9 years) and 2018 (mean 73.5 years) EUREQUO reports [6,7], with a majority of women. e percentage of eyes with prior pathologies and preoperative conditions increasing the surgical complexity (28.55% and 11.1% respectively) was similar in our study to those in the previous reports [6,9,10].…”
Section: Discussionmentioning
confidence: 79%
“…As regards refractive outcomes, our results also compare favorably with the recent reports. Mean absolute error between target and postoperative spherical equivalent was [21], and the EUROQUO report on refractive outcomes including surgeries performed in 2014 and 2015 found a mean absolute biometry prediction error of 0.42 D (SD 0.52) and 72.7% of eyes within 0.5 D of target [7]. Patients implanted with multifocal IOLs expect to be spectacle independent, and in order to achieve this and to optimize IOL performance, postoperative refraction should be close to emmetropia.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…ecently, a large multinational database study on intraocular lens (IOL) predictability including 282,811 cases showed that the mean absolute spherical equivalent (SE) prediction error after cataract surgery was 0.42 diopters (D) and 72% of eyes were within ±0.50 D of predicted SE. 1 In addition to various factors, such as coexisting eye diseases and surgical complications, the authors stated that the influence of postoperative residual astigmatism was considerable in their study. 1 Although toric intraocular lenses (IOLs) are a major advance in compensating corneal astigmatism in the course of cataract surgery, residual postoperative astigmatism remains a concern, with more than one-third of patients not reaching the targeted refraction after toric IOL implantation.…”
mentioning
confidence: 97%
“…So zdokonaľovaním techniky operácií a biometrických metód sme sa výrazné posunuli oproti prvej Ridleyho šošovky. Viac ako 90% operovaných očí dosahuje pooperačnú refrakciu (udanej v sférickom ekvivalente) v rozmedzí +/-1 D [2]. Na celkový výsledok operácie katarakty vplýva mnoho faktorov.…”
Section: úVodunclassified